A CASE REPORT OF COMPLICATED UROLITHIASIS IN MIXED TABBY TOM CAT - Faradina, Elfani Sarah (Journal of Veterinary and Animal Sciences, 2023)
The most common disease affecting felines urinary tract is urolithiasis. Urolithiasis is a disease caused by the formation of crystals or uroliths in the urinary tract. A 5 year old mixed-breed tom cat presented to the Veterinary Teaching Hospital of Udayana University for having haematuria, diminished urine and dysuria when urinating for the past nine days. Additional examination used is a complete blood count, ultrasonography, and urine sediment observation. An ultrasonography exam shows hyperechoic floating particles inside the urinary vesicle lumen, and urine sedimentation microscopy exam shows magnesium ammonium phosphate and calcium oxalate crystals. The final diagnosis was urolithiasis due to struvite and calcium oxalate crystals along with a dubious-fausta prognosis. The injections given were the antibiotic Cefotaxime (IM), and anti-inflammatory drug Tolfenamic Acid (SC). Animals also prescribe drugs such as Dexamethasone for 5 days, Cefixime for 6 days, and Kejibeling® orally for 5 days. Subsequently, seven days after the initial treatment, the feline can urinate smoothly.